Transparansi Pengelolaan Keuangan Pura Agung Asem Kembar dalam Bingkai Yadnya - I Putu Heri Hermawan; Lucy Sri Musmini (Jurnal Ilmiah Akuntansi dan Humanika, 2021)
This research aims to find out how the application of transparency in Pura Agung Asem Kembar as a public temple as well as the role of Yadnya in the existence of the temple. The data used in this study is primary data with structured interview and observation methods, as well as secondary data from documentation studies. The object of this research is Pura Agung Asem Kembar, the informants are the temple's manager (Pengempon) and visitors (Pemedek). The technique of obtaining data by triangulation method analyzed with three stages, namely data reduction, data display, and conclusion drawing. The result is the application of transparency in Pura Agung Asem Kembar is very low only the delivery of incoming funds without being followed by the delivery of cash expenditures. This phenomenon does not affect the performance of the temple's manager (pengempon) because of the existence of Yadnya as the basis of trust in the administrator of Pura Agung Asem Kembar.